KAJIAN DISTRIBUSI PANGAN POKOK BERAS DI KABUPATEN KEPULAUAN TALAUD - Eyverson Ruauw (AGRI-SOSIOEKONOMI, 2015)
This study aims to determine the various models of distribution channels / staple food marketing and analyze the performance of the market of each channel of distribution / marketing of staple food to the people in Talaud Islands District. Primary data were obtained through direct observation in the field and in-depth interviews (depth) by using a list of questions (questionnaire) which had been prepared in advance to the institutions of marketing / distribution of food.Â  Determination of the respondents in this study was conducted with a purposive sampling method and method snowbow of respondents key (key Pearson) of any marketing agencies. The results showed that the distribution of milled rice in the District of Talaud Islands only one pattern involving several marketing agencies, namely the village traders, wholesalers and retailers of Manado city in town Lirung Talaud Islands, while for rice packaging of Surabaya, the distribution includes agencies marketing Mananado local distributor, wholesaler in the city of Manado and retailers in town Lirung Talaud Islands. Also the results of the study showed that the total marketing margin is formed on the pattern of distribution channels milled rice food staples in Talaud Islands amounted to Rp2.500,00 per kg, with a total marketing costs amounted to Rp413 per kg, while for rice packaging, total marketing margin formed on the pattern of distribution channels staple food rice krmasan in District Talaud Islands is Rp 3.500,00 per kg, with a total marketing costs Rp454 per kg. The amount of the farmer's share of the milled rice marketing in District of Talaud Islands amounted to 73.68%, where the farm-gate price of Rp7,000 per kg and prices at the consumer level of Rp9,500 per kg. The ratio of cost advantages in marketing agency traders village is very large compared to the traders in the city of Manado and retailers in the City Lirung. Cost benefit ratio was lowest in the large trader marketing agencies in the city of Manado.